2017
DOI: 10.1021/acs.energyfuels.6b02941
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Measurement of Laminar Burning Velocity and Flammability Limits of Landfill Gas at Atmospheric and Elevated Pressures

Abstract: Landfill gas (LFG) produced from depletion of biological waste has the potential to become one of the main energy resources in the future. In this study, laminar burning velocity (ul), Markstein length, and flammability limits of different compositions of landfill gas (LFG) are measured using the Schlieren flame front visualization method in an 11 liter constant volume combustion chamber. Three common compositions of LFG with carbon dioxide (CO2) volumetric fraction of fuel ranging from 0.3 to 0.5 are examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…These results are supported by the investigation of Schlieren images provided in Figure 4(a) and Figure 4(b). Many studies have also suggested similar relationship between CO2 concentration and initial mixture pressure toward laminar burning velocity value found in this study [9,13,[16][17][18][19]22].…”
Section: Experimental Setup and Conditionssupporting
confidence: 86%
See 3 more Smart Citations
“…These results are supported by the investigation of Schlieren images provided in Figure 4(a) and Figure 4(b). Many studies have also suggested similar relationship between CO2 concentration and initial mixture pressure toward laminar burning velocity value found in this study [9,13,[16][17][18][19]22].…”
Section: Experimental Setup and Conditionssupporting
confidence: 86%
“…The laminar burning velocity can be measured from spherically propagating flames by recording the increasing rate of the flame radius with respond to time [16,17]. There has been a series of studies on the effects of CO2 and initial mixtures pressure on laminar burning velocity of CH4 [18][19][20][21][22][23]. Some studies suggested that as the percentage of CO2 in fuel mixture increases, biogas laminar burning velocity decreased [10,[19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, they have reported that an optimum jet-to-jet spacing exists for parallel burners at each Reynolds number. In a recent cross-sectional study, Askari and Ashjaee investigated the effect of the pressure on the laminar burning velocity and flammability limits of landfill gas, where their results indicate that a reducing pressure increases the laminar burning velocity. Studies over the past few years have provided important information on the effects of mixing conditions for various fuels, experimentally , and numerically …”
Section: Introductionmentioning
confidence: 99%